USAGE OF SUPPORTING PAD FOR SUPINE PCNL: A SINGLE CENTER EXPERIENCE - Hakim, Rizky Lukman; Birowo, Ponco (Indonesian Urological Association, 2022)
Objective: This study aims to compare the safety, efficacy, and other surgical outcomes of supine PCNLs performed with and without the use of supporting pad. Material & Methods: We enrolled 27 patients who undergone PCNL procedure with supine position for renal stones with all sizes between January - December 2019. Divided into two groups, operated with and without supporting pad, with 13 and 14 patients respectively. Inclusion criteria are patients with renal stones, including staghorn, multiple calyx, and proximal ureteral stones. Meanwhile, pediatric patients under 12 years old, uncorrectable bleeding disorders, active urinary infection, and pregnancy are excluded. Results: Our observation showed no statistically significant difference between the two groups, although blood loss and length of stay in supporting pad showed better results. A statistically significant difference was found in stone-free-rate (P = 0.006) favoring in supine PCNL with supporting pad. Conclusion: Supine PCNL with support padding may be a safe and more effective choice to treat renal stones. Nevertheless, the patient’s anatomic variations may influence this. Thus, a prospective study with a larger population is needed to verify our outcomes.